A Syndetic Coordinator of Compound Sentences Analysis in the Introduction of “Quiet” - I Made Kevin Raditya; Ni Putu Cahyani Putri Utami (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Coordination is a key syntactic device that links clauses to build coherent and rhetorically effective discourse. This study focuses on identifying the types of syndetic coordinators in compound sentences and examining their semantic relations in the introduction of Susan Cain’s Quiet: The Power of Introverts in a World That Can’t Stop Talking. The study aims to provide insight into how coordination strategies in nonfiction introductions contribute to both sentence structure and meaning. The analysis applied Quirk and Greenbaum’s (1974) framework to classify semantic implications and the application of constituent structure representation to illustrate syntactic patterns. The data were collected through an observation method and analysed using a descriptive qualitative approach. Based on the results, a total of 5 instances of “but,” 1 instance of “or,” and 6 instances of “and” were found. The conjunction “but” served an adversative function, expressing either contrast or denial of expectation; “or” introduced mutually exclusive alternatives in a rhetorical question; and “and” performed additive functions, indicating either temporal sequence or pure addition, with some cases of subject ellipsis. The frequent use of “and” indicates the author’s preference for smooth additive and sequential linking to develop narrative flow in the introduction. These findings reveal that the syntactic form of each coordinator reinforces its semantic role, demonstrating the close relationship between structure and meaning in nonfiction prose.